The Effect of Vitamin D Supplementation on Sputum Conversion, Erythrocyte Sedimentation Rate and Neutrophil-Lymphocyte Ratio in Pulmonary Tuberculosis Patients – A Randomized Controlled Trial - Sonjaya, Muchamad Regi; Isa, Mohamad; Yasmina, Alfi; Ansori, Isa; Nurrasyidah, Ira; Kusumawardhani , Erna (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND : The health issue of pulmonary tuberculosis (TB) remains a concern in Indonesia. Vitamin D supplementation is one way to manage tuberculosis, which is a crucial case control metric. It is anticipated that vitamin D's anti-inflammatory properties will lower erythrocyte sedimentation rate (ESR) and inflammatory indicators, hence speeding up sputum conversion. AIMS :  To analyze the effect of vitamin D supplementation on sputum conversion, ESR and neutrophil-lymphocyte ratio (NLR) among pulmonary tuberculosis patients METHOD : Patients with pulmonary tuberculosis who were treated as outpatients at Ulin Banjarmasin Hospital and Pekauman Health Centre between May-July 2024 and who satisfied the study's inclusion requirements were included in the randomised controlled trial. Subjects were randomly divided into 2 groups (19 subjects in the treatment group and 19 subjects in the control group) using random selection with sealed envelopes. The treatment group received antituberculosis drugs (ATD) and vitamin D supplementation at a dose of 10,000 IU/day for eight weeks after the initiation of TB therapy, while the control group received ATD and a placebo. ESR and NLR examinations were performed prior to treatment, in weeks 4 and 8, whereas sputum evaluations were conducted at weeks 2, 4, 6, and 8. Statistical Product and Service Solutions (SPSS) was used for data analysis. P-value <0,05 was significant statistically. RESULT :  The study subjects were 38 pulmonary TB patients, most of whom were women (65.0%) with an average age of 50.42 ± 18.61 years. Overall, during the 8 weeks of intervention, there was a significant effect of vitamin D supplementation on sputum conversion (OR = 1.61, 95%CI = 0.030-0.931, p = 0.037). There was no significant effect of vitamin D supplementation on NLR (regression coefficient = 0.549, 95%CI = -1.769-2.858, p = 0.641) and ESR (regression coefficient = -5.529, 95%CI = -20.658-9.599, p = 0.474). CONCLUSION : Vitamin D supplementation significantly affects sputum conversion. In the 8th week, almost all subjects who initially had positive BTA became negative. But does not significantly affect ESR and NLR.